Seguridad: perspectivas teóricas y su evolución reciente - Segura, Luis Diego (2013)
This article reviews the security approaches that have been implemented in the region based on the four key elements that the different models responds to, these are the reference object,the source of the threats, the scope of action and resources to respond, and finally the dynamic of threats, dangers and urgency. Finally, presents a deeper analysis of the effects that these developments have had in Central America.